Tunnel-convective air-assisted spraying technology for improving droplet deposition on hedgerow vines - Wen, Zhenjie; Qiu, Wei; Zhang, Zhentao; Ding, Weimin; Lv, Xiaolan; Ahmad, Fiaz; Wang, Hui (International Journal of Agricultural and Biological Engineering, 2021)
Given the impermeability, larger dosage, and higher drift of pesticides used in modern hedgerow vine canopies, a novel tunnel-convective air-assisted spraying technology was proposed. Mechanized spraying equipment with high penetration and low drift was developed. The air-assisted system of this equipment was centrosymmetric, and the fan type was cross-flow. The fan outlet width was 138 mm and the air duct’s main body followed a logarithmic spiral profile, based on parallel flow theory. The external diameter of the impeller was 157 mm, which was fixed into a barrel structure by 23 strong forward-curved blades, each being 1 mm thick. The central angle of the blades was 108°, and the ratio of the internal and external diameters was 0.81. The impeller and air duct served as guides to circulate and reciprocate airflow around the crown, forming a tunnel-convective air-assisted to the vine. Using MATLAB interpolation, the airflow trajectory of the air convection circulation in the door-shaped cover was obtained. The velocity field distribution test showed that, in the case of a canopy, there were tunnel-convective circulating airflows with high velocity on both sides and uniform velocity in the middle of the canopy. Due to the tunnel-convective air-assisted spraying technology, the vertical distribution uniformity of spray deposition has been significantly improved, spray penetration has been enhanced, penetrability has been effectively improved, and droplets on the ground and in the air have been significantly reduced. The results of this study can assist in providing further optimization and improvement of plant protection machinery. The new tunnel-convective air-assisted spraying technology may be a more favorable choice for future spray applications and the environment.Keywords: plant protection, air-assisted, hedgerow vines, cross-flow fan, droplet depositionDOI: 10.25165/j.ijabe.20211406.6482Citation: Wen Z J, Qiu W, Zhang Z T, Ding W M, Lyu X L, Ahmad F, et al. Tunnel-convective air-assisted spraying technology for improving droplet deposition on hedgerow vines. Int J Agric & Biol Eng, 2021; 14(6): 9–18.